Multilingual Linguistic Landscape in Lombok Tourism Area as a Social Education Media and Representation of Cultural Identity - Arini Noor Izzati; Brillianing Pratiwi; Rahma Dewi Hartati; Juliana Simangunsong (Raja Zulkarnain Education Foundation, 2026)
This study explores how multilingual signage is used in tourism areas in Lombok and considers its role in shaping both communication practices and cultural identity. The research adopts a qualitative descriptive approach with a sociolinguistic perspective, drawing on observations, documentation, and a limited number of interviews. The data consist of various forms of public signage, including direction signs, shop names, advertisements, and tourist information boards found across major tourist destinations. The findings suggest that most signage combines Indonesian and English, reflecting a clear emphasis on accessibility for a diverse range of visitors. From a practical standpoint, this appears to support tourists in navigating the environment, as indicated by respondents’ experiences. At the same time, the relatively limited presence of the local Sasak language points to a less visible role of local identity in public space. Taken together, these patterns indicate that while the linguistic landscape functions effectively as a communication tool, its potential to represent local culture is not yet fully realized. This highlights the importance of considering both communicative needs and cultural representation in the development of tourism spaces.